Realita Pendidikan Islam di Indonesia Pasca Kemerdekaan: Perkembangan, Tantangan, dan Prospek Masa Depan - Hidayat, Rahmat; Nisa, Khairun; Zaini, M.; Safitri, Dewi; Astini, Baiq Ida (IIQ An Nur Yogyakarta, 2024)
This study aims to conduct a Systematic Literature Review on the realities of Islamic education in Indonesia post-independence, focusing on its development, challenges, and future prospects. The literature sources used are using indexing machine with a publication range from 2014 to 2024. The findings indicate significant efforts to enhance the quality and relevance of education through the integration of technology, policy changes, and international cooperation. However, several gaps still need to be addressed, including issues related to resources, infrastructure, and the quality of teachers, which pose serious obstacles to the effectiveness of Islamic education. Additionally, challenges related to the curriculum's relevance to societal needs and societal recognition of Islamic education also need to be overcome. This study provides important insights for the development of Islamic education in Indonesia, highlighting the roles of technology, policy, and international cooperation in improving its quality and relevance in the future.